Constructing vector having TI-DNA contained coda gene and some transplants selection assitance structures - Thu Huong, Bui Thi; Huong, Ho Thi; Thang, Bui Van; Son, Le Van; Binh, Le Tran (Academia Journal of Biology, 2014)
Adverse factors from the environment, such as, drought and salinity, water logging and high temperatures often cause serious effects on the growth and development of plant or crop yield. CodA gene found in Arthrobacter globiformis encode for choline oxidase involved in the biosynthesis of glycine betaine have been shown to be transferable to some plants which help them resist such adverse conditions. Vector recombinant pCAMBIA1301 has been successfully designed with the codA gene. Additionally, the Ti-DNA region contains the remarkable gene Gus and a hygromycine resistance selected gene that also can help researcher select transgenic plants quickly and easily. The recombinant vector structure is also successfully transferred into A. tumefacien that have tested by PCR. The vector was ready transferred in to tobacco in order to produce valuable tolerance varieties to salt.